Population Genomic Analysis of Base Composition Evolution in Drosophila melanogaster - Poh, Yu-Ping (Oxford University Press, 2012)
The relative importance of mutation, selection, and biased gene conversion to patterns of base composition variation in Drosophila melanogaster, and to a lesser extent, D. simulans, has been investigated for many years. However, genomic data from sufficiently large samples to thoroughly characterize patterns of base composition polymorphism within species have been lacking. Here, we report a genome-wide analysis of coding and noncoding polymorphism in a large sample of inbred D. melanogaster strains from Raleigh, North Carolina. Consistent with previous results, we observed that AT mutations fix more frequently than GC mutations in D. melanogaster. Contrary to predictions of previous models of codon usage in D. melanogaster, we found that synonymous sites segregating for derived AT polymorphisms were less skewed toward low frequencies compared with sites segregating a derived GC polymorphism. However, no such pattern was observed for comparable base composition polymorphisms in noncoding DNA. These results suggest that AT-ending codons could currently be favored by natural selection in the D. melanogaster lineage.